PENELANTARAN ORANG TUA DALAM LINGKUP RUMAH TANGGA PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA: PENELANTARAN ORANG TUA DALAM LINGKUP RUMAH TANGGA PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Wardah Nuroniyah (QAWWAM, 2019)
Abstract One of the acts of domestic violence against people in the household sphere is neglect. Parental neglect is negligence of the child towards the biological mother's father who has a dependency in physical needs (negligence to provide adequate food, clothing, or hygiene), and emotional (negligence to provide care or affection). neglect of parents is included in the form of lawlessness to parents because parents have rights to their children. So that for each perpetrator of neglect parents must be subject to sanctions. This study aims to answer the questions that formulate the problem: "What is the view of Islamic law and positive law in Indonesia on neglect of parents" and "What are the sanctions for perpetrators of neglect of parents according to Islamic law and positive law in Indonesia". This study uses qualitative research, data collected by means of literature (library research) are then analyzed. As for the results of this study: 1) Neglect of parents in Islamic law and in positive law in Indonesia is prohibited, because in Islamic law people who do neglect are sinful, while in positive law in Indonesia neglect is included in violence. 2) Sanctions for perpetrators of neglect of parents in the perspective of Islamic law and positive law in Indonesia are criminal sanctions, but in Islamic law it is called jarimah ta'zir and the sanctions are not only that but there are other sanctions, namely big sins, all deeds are not accepted by Allah SWT, will not enter heaven, hated by Allah SWT. Keywords: Neglect, Parents, Sanctions, Islamic Law, Positive Law in Indonesia.